Effects of thermal treatment on phase transitions and on the mechanical relaxation in poly(vinylidene fluoride) - Alves, Neri [UNESP]; Cardoso, C. X. [UNESP]; Job, A. E. [UNESP]; Giacometti, J. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2002)
This work reports on the effects from thermal treatment in poly(vinylidene fluoride), PVDF, obtained with differential scanning calorimetry (DSC) and dynamic thermal analysis (DMA) measurements. It is shown that in successive DMA measurements performed with one sample the α relaxation peak almost disappears while the γ′ peak appears. The α relaxation peak, at ∼100°C in DMA measurements, is attributed to the preferential orientation of chains in the amorphous phase while the γ′ relaxation peak, at ∼50°C, is related to the thermal treatment to which the sample was submitted.
Keywords: Dielectric relaxation; Differential scanning calorimetry; Differential thermal analysis; Fluorine containing polymers; Heat treatment; Molecular orientation; Molecular structure; Phase transitions; Thermal effects; Polyvinylidene fluoride; Semicrystalline polymers; Piezoelectric materials